Meandering rivers' morphological changes analysis and prediction – a case study of Barak river, Assam. Issue 2 (17th May 2022) - Nath, Apurba; Ghosh, Susmita
Abstract: Morphological studies are vital for water resources management, riverbank development, and flood mitigation. In this study, the sinuosity index and bank erosion were used to detect and quantify morphological changes using Landsat data (1990–2020) in the Barak river, India. The morphological changes were investigated in protected areas to analyze the effectiveness of existing protective structures on bank migration, which helps formulate better riverbank restoration plans. Using monthly discharge data from two stream gauge stations, the Seasonal Autoregressive Integrated Moving Average (SARIMA) models were developed. The extensive sediment transportation in the region necessitates studying both the river flow and morphological changes. The developed SARIMA model was used to predict river discharges up to 2025, being trained with data from 2006 to 2015. The validation of the model (2016–2018) shows that the mean absolute percentage error for discharge at two gauging stations is 29.78 and 23.52%, respectively. The analysis shows that the sinuosity index and bank erosion were inversely proportional. The SARIMA model showed that the future monthly discharge in the case study could be substantially higher than the observed series and affect river erosion simultaneously. This approach applies to many other meandering river management and identifies future morphological changes. HIGHLIGHTS: Sinuosity index and riverbank erosion both are inversely proportional. The efficiency of protection structures must be determined for alluvial river management. Inadequate protection structure planning might lead to downstream hazards. The SARIMA model can accurately estimate future discharge by which segment-by-segment future morphological analyses are possible. Graphical Abstract